Strategic management and business policy : achieving sustainability - Wheelen, Thomas L.; Hunger, David (Boston, Massachusetts : Prentice-Hall, 2010)
This edition introduces a new theme that runs throughout all 12 chapter : environmental sustainability.
Part one : Introduction to strategic management and business policy -- Part two : Scanning the environment -- Part three : Strategy formulation -- Part four : Strategy formulation -- Part five : Introduction to case analysis -- Part six : WEB chapters other issues -- Part seven : Cases in strategic management
Includes index.
Keywords: STRATEGIC MANAGEMENT